Mapping Creative Careers: Global Bibliometric Review (Management and Connections Journal, 2025)
This study conducts a bibliometric review on creative careers, aiming to map global scientific production, identify research gaps, and propose a future research agenda. A total of 166 articles published in the Web of Science and Scopus databases were analyzed using RStudio® with the Bibliometrix® package and VOSviewer® for the bibliometric analyses. The results indicate a significant growth in publications on creative careers since 2016, and the co-citation networks reveal consolidated theoretical clusters and emerging topics, such as neuroscience and mental health in connection with creative careers. The proposed agenda suggests investigations on digitalization, segmentation of creative sectors, post-pandemic survival strategies, as well as studies employing biographical methods. This study contributes to the theoretical and conceptual advancement of the field, highlighting multidisciplinarity as a central element.
Keywords: creative careers; creative work; scopus; web of science; creative industries